Gerbode defect following surgical mitral valve replacement and tricuspid valve repair: a case report. Issue 2 (30th December 2020) - Haraf, Rebecca H; Karnib, Mohamad; El Amm, Chantal; Plummer, Sarah; Bocks, Martin; Sabik, Ellen M
Abstract: Background: Gerbode defect is a congenital or acquired communication between the left ventricle and right atrium. While the defect is becoming a more well-recognized complication of cardiac surgery, it presents a diagnostic and therapeutic challenge for providers. This case highlights the predisposing factors and imaging features that may assist in the diagnosis of Gerbode defect, as well as potential approaches to treatment. Case summary: We report a patient with severe mitral stenosis as a result of remote mediastinal radiation who underwent extensive decalcification during surgical mitral valve replacement and tricuspid valve repair. Following the procedure, he developed progressive heart failure refractory to medical management. Extensive workup ultimately led to the diagnosis of iatrogenic acquired Gerbode defect. Close collaboration between adult cardiology, cardiothoracic surgery, and the congenital cardiology services led to an optimal treatment plan involving percutaneous closure of the defect. Discussion: Gerbode defect is a rare complication of invasive procedures involving the interventricular septum or its nearby structures. An understanding of the key echocardiographic features will aid providers in timely diagnosis. Percutaneous repair should be strongly considered for patients who may be poor surgical candidates.